Oxidative phosphorylation in HIV-1 infection: impacts on cellular metabolism and immune function - Rodriguez, Natalia Rodriguez; Fortune, Trinisia; Hegde, Esha; Weinstein, Matthew Paltiel; Keane, Aislinn M.; Mangold, Jesse F.; Swartz, Talia H. (Frontiers in Immunology, 2024)
Human Immunodeficiency Virus Type 1 (HIV-1) presents significant challenges to the immune system, predominantly characterized by CD4+ T cell depletion, leading to Acquired Immunodeficiency Syndrome (AIDS). Antiretroviral therapy (ART) effectively suppresses the viral load in people with HIV (PWH), leading to a state of chronic infection that is associated with inflammation. This review explores the complex relationship between oxidative phosphorylation, a crucial metabolic pathway for cellular energy production, and HIV-1, emphasizing the dual impact of HIV-1 infection and the metabolic and mitochondrial effects of ART. The review highlights how HIV-1 infection disrupts oxidative phosphorylation, promoting glycolysis and fatty acid synthesis to facilitate viral replication. ART can exacerbate metabolic dysregulation despite controlling viral replication, impacting mitochondrial DNA synthesis and enhancing reactive oxygen species production. These effects collectively contribute to significant changes in oxidative phosphorylation, influencing immune cell metabolism and function. ATP generated through oxidative phosphorylation can influence the metabolic landscape of infected cells through ATP-detected purinergic signaling and contributes to immunometabolic dysfunction. Future research should focus on identifying specific targets within this pathway and exploring the role of purinergic signaling in HIV-1 pathogenesis to enhance HIV-1 treatment modalities, addressing both viral infection and its metabolic consequences.